Endocrine and metabolic disorders in adolescent and adult patients born small for gestational age: Long term disorders in patients born SGA - Talarico, Valentina; Nicoletti, Angela; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
Children born small for gestational age (SGA), defined by a birth weight and/or length standard deviation score (SDS) of < −2 based on an appropriate reference population, represent a diverse group due to multiple underlying causes of reduced growth. This classification results in a heterogeneous patient cohort. SGA children are prone to endocrinological and metabolic issues not only in childhood but also extending into adolescence and adulthood. This population faces elevated health risks, including persistent short stature, premature adrenarche, pubertal development alterations, neurocognitive problems, and metabolic syndrome. Insulin resistance emerges as a pivotal factor c nht6j7ikontributing to these metabolic complications, prominently featuring obesity, insulin resistance, hypertension, and an increased risk of type 2 diabetes mellitus in adulthood. These medium- to long-term complications significantly impact their quality of life. Growth hormone (GH) therapy for short children born SGA facilitates height normalization throughout childhood, adolescence, and into adulthood. Catch-up growth, however, correlates with heightened risks of obesity, insulin resistance, and metabolic syndrome. Conversely, those without catch-up growth tend to exhibit pronounced short stature and cognitive dysfunction. Given these determinants, comprehensive management and clinical monitoring of SGA children should commence in the neonatal period and extend into adulthood. Recognizing and addressing these challenges early in life can mitigate the long-term impact on health and well-being, emphasizing the importance of a lifelong approach to their care.